Protocols for Microcontrollers Networks - López, Ricardo A. (2011)
The microcontrollers are embedded in our way of life and are found in many devices. The ability of Very High Scale Integration (VLSI) - with almost exponential growth in recent years makes these devices every day contain functions previously unthinkable. Therefore, a grouping of these networked devices creates a very powerful system, which equipped with a standard protocol that allows interconnection to the Internet gives you a virtually unlimited range of scalability. For these reasons, this thesis studied the implementation of a network of microcontrollers, defining functions equivalent to those with Supervisory Control and Data Acquisition (SCADA) of great scale. Based on the definition we have, we studied among others, the protocols of communications layers to reach two of the most popular implementations used in industrial environments: Rs485 and Ethernet. While the former is much older, it remains still active and has been promoted from creating compatible interfaces, due to Rs485’s high immunity to electrical noise that provides a transparent interface over fiber. The second, more modern, already have set a trend because of its ubiquity and extent of benefits.